Controle E Internação Entre O Público E O Privado: Hospital Psiquiátrico Do Juquery E Sanatório Pinel De Pirituba (1929-1934) - Lanzellotti, Tuanny Folieni Antunes [UNIFESP] (2018)
The Debates On Mental Health Became Prominent In The Late Nineteenth Century With The Emergence Of Psychiatry As A Medical Specialty And Remained Prominent Throughout The Twentieth Century. A Context Of Intense Urban Transformations, In Which Aspects Related To Modernization And Progress Were Added, Deepening The Search For A Sanitized And Orderly City. It Is Thinking In Questions Such As Those That This Research Develops, Having As Primary Source The Medical Records Of The Psychiatric Hospital Of Juquery And Sanatorio Pinel Of Pirituba, Founded In 1898 And 1929, Respectively. It Is Intended To Identify The Profile Of The Patients Considered Mentally Ill, The Possible Reasons That Assigned A Portion Of The Population To Isolation In This Context And The Different Agents And Mechanisms Of Hospitalization. Observing Similar And Distinct Characteristics Between The Patients And The Circumstances Under Which They Were Submitted, Specifically In The Period From 1929 To 1934, When Both Institutions Were Under The C